PENGARUH PENGAWASAN TERHADAP DISIPLIN KERJA PEGAWAI PADA DINAS KOMUNIKASI DAN INFORMATIKA PROVINSI SUMATERA SELATAN - Rohmial . (Jurnal Keuangan dan Bisnis, 2019)
The purpose of this study was to examine the effect of supervision on the work discipline of employees at the Communication and Information Agency of South Sumatra Province, in this study the authors used a type of quantitative research. The samples taken in this study were 53 people. The data analysis technique used in this study is simple linear regression and, analysis of the coefficient of determination. The results of the study show that all existing instruments are declared valid and realistic and from the regression calculation it is proven that there is an influence between supervision and work discipline. The results of regression analysis obtained a regression equation = 11.456 + 0.761X. The verification test of the regression equation was obtained from the t-test = 8.522 with a probability of 0.0000 <0.05. This shows that supervision influences the work discipline of employees at the Communication and Information Agency of South Sumatra Province. The magnitude of influence is also seen from the coefficient of determination which has a value of 0.587 or 58.7% and the rest of the work discipline of employees is influenced by other factors besides supervision of 41.3%.